The Ser96Ala variant in histidine-rich calcium-binding protein is associated with life-threatening ventricular arrhythmias in idiopathic dilated cardiomyopathy - Arvanitis, DA; Sanoudou, D.; Kolokathis,F.; Vafiadaki, E.; Papalouka, V.; Kontrogianni-Konstantopoulos, A.; Theodorakis, GN; Paraskevaidis,I.A.; Adamopoulos, S; Dorn, G. W., 2nd; Kremastinos, D.T.; Kranias, EG (Eur Heart JEur Heart JEur Heart J, 2008)
AIMS: To investigate whether genetic variants of the histidine-rich calcium (HRC)-binding protein are associated with idiopathic dilated cardiomyopathy (DCM) and its progression. METHODS AND RESULTS: We screened 123 idiopathic DCM patients and 96 healthy individuals by single-strand conformation polymorphism analysis and direct sequencing for genetic variants in HRC. Six polymorphisms were detected: Leu35Leu (A/G), Ser43Asn (G/A), Ser96Ala (T/G), Glu202_Glu203insGlu (-/GAG), Asp261del (GAT/-), and an in-frame insertion of 51 amino acids at His321. The analysis of their frequencies did not reveal any significant correlation with DCM development. However, the Ser96Ala polymorphism exhibited a statistically significant correlation with the occurrence of life-threatening ventricular arrhythmias. During a follow-up of 4.02 +/- 2.4 years, the risk for ventricular arrhythmias was higher (HR, 9.620; 95% CI, 2.183-42.394; P = 0.003) in the Ala/Ala patients, compared with Ser/Ser homozygous patients. On multivariable Cox regression analysis, the Ser96Ala polymorphism was the only significant genetic arrythmogenesis predictor in DCM patients (HR, 4.191; 95% CI, 0.838-20.967; P = 0.018). CONCLUSION: The Ser96Ala genetic variant of HRC is associated with life-threatening ventricular arrhythmias in idiopathic DCM and may serve as an independent predictor of susceptibility to arrhythmogenesis in the setting of DCM.
Keywords: Adult; Arrhythmias, Cardiac/*genetics; Calcium-Binding Proteins/*genetics; Cardiomyopathy, Dilated/*genetics/physiopathology; Death, Sudden, Cardiac/prevention & control; Defibrillators, Implantable; Disease Progression; Female; Genotype; Humans; Male; Middle Aged; Myocardial Contraction/physiology; Polymorphism, Genetic/*genetics